A new earthworm eel of the genus Chaudhuria from the Ayeyarwaddy River Drainage, Myanmar (Teleostei: Synbranchiformes: Chaudhuriidae) - Britz, Ralf (Zootaxa, 2010)
Chaudhuria ritvae, new species, from the lower Ayeyarwaddy River Drainage, southern Myanmar, is distinguished from C. caudata by a greater number of caudal vertebrae, shorter jaws, larger and broader ribs, neural arches of vertebrae without fenestration, absence of spots associated with base of dorsaland anal-fin rays, sparse body pigmentation consisting of only minute widely separated melanophores, and absence of pigmentation along pectoral-fin rays. It differs from its only other congener, C. fusipinnis, by having the dorsal and anal fins separate from the caudal fin, by a smaller number of dorsaland anal-fin rays, by a greater number of caudal-fin rays and by the presence of teeth on hypobranchial 3.